2022
DOI: 10.1007/s12525-022-00540-4
|View full text |Cite
|
Sign up to set email alerts
|

Data-driven forwarding: a typology of digital platforms for road freight transport management

Abstract: The omnipresence of digital platforms (DPs) across industries yields platform-based business concepts that disrupt the road freight market, enabling the digitalization of road freight transport management (RFTM). However, the data-driven service capabilities of DPs in supporting RFTM are manifold, and platform research provides opportunities to explore the emerging digital business concepts following the core process of transport management systems (TMSs). This, in particular, results from the side of road fre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 56 publications
0
7
0
3
Order By: Relevance
“…Likewise, the application of telematics for FTAs reveals IoT service capabilities based on transport monitoring, tracking, and automated notifications in case of deviations in conditions (e.g., temperature), particularly for the food industry (Verdouw et al 2016;Li et al 2017;Salah et al 2020). The real-time information and automatization of telematics-enabled FTAs allow transport stakeholders to achieve visibility and optimizations over freight operations based on the gained data yielding data-driven business models in logistics (Möller et al, 2020;Heinbach et al 2022a). That is, for instance, an automated billing service offered to customers once the FTA equipped with telematics has arrived in a geofenced area.…”
Section: Mobile Telematics For Freight Operationsmentioning
confidence: 99%
See 3 more Smart Citations
“…Likewise, the application of telematics for FTAs reveals IoT service capabilities based on transport monitoring, tracking, and automated notifications in case of deviations in conditions (e.g., temperature), particularly for the food industry (Verdouw et al 2016;Li et al 2017;Salah et al 2020). The real-time information and automatization of telematics-enabled FTAs allow transport stakeholders to achieve visibility and optimizations over freight operations based on the gained data yielding data-driven business models in logistics (Möller et al, 2020;Heinbach et al 2022a). That is, for instance, an automated billing service offered to customers once the FTA equipped with telematics has arrived in a geofenced area.…”
Section: Mobile Telematics For Freight Operationsmentioning
confidence: 99%
“…Given the increasing digital competition in the transport market due to emerging IoT technologies and digital platforms yielding digital business models by startups (Möller et al 2020;Heinbach et al 2022a), visibility in transport chains has emerged as a commodity service for shippers and consignees. Against this issue, our analysis revealed that transport operators have a strong interest in the detection of irregularities in the equipment used to observe the performance of their fleet with a focus on operational efficiency and customer satisfaction.…”
Section: Anomaly Detection and Automation Based On Event Specificatio...mentioning
confidence: 99%
See 2 more Smart Citations
“…Die Nutzung des IT-gestützten Angebots von Diensten orientiert sich dabei an den Geschäftsprozessen der Transportdienstleister mit eigenem Fuhrpark und umfasst bspw. die Auftragsabwicklung, die Sendungsverfolgung, die Routen-und Tourenplanung sowie ein effizientes Fahrzeugmanagement (Heinbach et al 2022a).…”
unclassified